Martyr’s Memorial at Hutatma Chowk - Ghosh, Ayan (Jio Institute, 2023)
Flora Fountain shares the intersection of Dadabhai Naoroji Road, Mahatma Gandhi Road and Veer Nariman Road with “The Martyr with a Flame” memorial, which was added in 1961, and the intersection was renamed Hutatma Chowk in memory of those who were martyred during the Samyukta Maharashtra Movement (Movement for United Maharashtra).